A DFT Study of CO2 Hydrogenation on Faujasite‐Supported Ir4 Clusters: on the Role of Water for Selectivity Control. Issue 15 (23rd June 2016) - Szyja, Bartłomiej M.; Smykowski, Daniel; Szczygieł, Jerzy; Hensen, Emiel J. M.; Pidko, Evgeny A.
Abstract: Reaction mechanisms for the catalytic hydrogenation of CO2 by faujasite‐supported Ir4 clusters were studied by periodic DFT calculations. The reaction can proceed through two alternative paths. The thermodynamically favoured path results in the reduction of CO2 to CO, whereas the other, kinetically preferred channel involves CO2 hydrogenation to formic acid under water‐free conditions. Both paths are promoted by catalytic amounts of water confined inside the zeolite micropores with a stronger promotion effect for the reduction path. Co‐adsorbed water facilitates the cooperation between the zeolite Brønsted acid sites and Ir4 cluster by opening low‐energy reaction channels for CO2 conversion. Abstract : All about that water molecule : DFT calculations reveal two possible reaction paths for the CO2 reduction on the faujasite‐supported Ir4 clusters. The selectivity of this process can be controlled by the presence of water in the zeolite cages. The catalytic paths to formic acid can be realised only under water‐free conditions. In the presence of water, the reductive conversion to CO is preferred.